Understanding The Politics of International Law: A Case Study of The Israel-Palestine Conflict - Ansori Ansori; Godswill Owoche Antai; Paul Atagamen Aidonojie; Muwaffiq Jufri; Hassan Ismaila Adebowale (Lampung Journal of International Law, 2026)
The relationship between international law and international politics remains highly contested in the context of the Israeli-Palestinian conflict, which is shaped by complex legal, political, and historical factors. This study examines how international legal frameworks are interpreted and implemented within broader geopolitical dynamics. Using a doctrinal legal research approach, the study analyzes primary legal sources, including international conventions, United Nations Security Council resolutions, advisory opinions of the International Court of Justice, and proceedings of the International Criminal Court, supported by academic literature and policy documents. The analysis focuses on the application of legal principles related to occupation, self-determination, accountability, and dispute resolution in the Israeli-Palestinian conflict. The findings demonstrate that the enforcement of international law is significantly constrained by geopolitical interests, resulting in selective application and weakening claims of legal neutrality and universality. The study also finds that the effectiveness of international legal mechanisms depends not only on legal norms, but also on institutional impartiality and political commitment to accountability. These findings highlight the need for reforms that reduce politicization and strengthen the credibility of international legal enforcement in resolving global conflicts.